Iodine-Catalyzed Chemoselective Hydroamination Reaction Using 5-Mercaptotetrazoles Derivatives - Siddaraju, Yogesh (ACS Omega, 2018)
[Image: see text] Metal-free chemoselective hydroamination of styrene derivatives has been achieved with high chemoselectivity over sulfenylation of 1H-tetrazole-5-thiol using a catalytic amount of iodine. The scope of this methodology has been extended for the hydroamination of α-substituted styrene derivatives. This reaction involves a single-step C–N-bond formation under atom economical process. This eco-friendly method uses readily available and inexpensive iodine in a catalytic amount.